Investigation on the significance of numerical and physical parameters on a plane wall heat transfer - Dedhy Prihtiantoro (Multidisciplinary Innovations and Research in Applied Engineering, 2024)
Heat transfer is a process that underlines many engineering applications. Temperature distribution and heat flux of a part as an effect of heat load can be analyzed for technical and economic justification. Computation has been easier with the aid of computational software based on numerical methods. The numerical method is about approximation; therefore, validation is necessary to verify the accuracy. A comparison of numerical and analytical methods on a plane wall thermal analysis had confirmed that the result from ANSYS fluent satisfies the computation. The results were strengthened by the negligible error when comparing the analytical and numerical methods. An extended study was performed to further investigate the significance of numerical and physical parameters on the result. The numerical parameter does not seem to have a significant effect, yet the physical parameters do. The study can be employed to predict the generated heat flux from various parameters under predefined operating conditions.